(untitled) (International Journal of Food and Nutritional Sciences, 2023)
PSYCHOBIOTICS previously known as probiotics, live bacteria in human gut, has been an emerging field of research that speaks about psychological and physiological health benefits. Research based evidences provided comprehensive awareness of psychobiotics in treating psychiatric disorders such as schizophrenia, alzeihmer’s disease, anxiety, depression etc. it has also shown breathtaking proof in ameliorating cognitive functioning of brain. A significant role is being played by intestinal microbiota via activity of the microbiota-gut- brain axis a bi-directional communication on several functions of brain such as learning, memory etc. the present narrative research focused on the health benefits of psychobioticsin proper functioning and its impact in healing neurodegenerative disorders. The conclusions revealed that the gut microbiota has found to have profounding effect in curing mental illnesses also in improving the human cognition. Yet, more research has to be carried out to appendage the existing body of research that unravel the benefits in various domains of human life such as social, behavioural, language, conceptual and emotional etc.,